Child care directors’ perceptions of pedagogical leadership roles - Poirier, Amy (Kansas State University, 2020)
Pedagogical leadership encompasses the directors’ role in the instructional practices within child care centers, including supporting teachers in the implementation of curriculum. Research has shown that child care directors’ perceptions of their role in addition to their knowledge, experience, and beliefs affect the type of teacher-child interactions and instruction that they encourage and support within their centers. It is the quality of these teacher-child interactions that affect child outcomes in addition to overall program quality. Therefore, directors’ failure to provide pedagogical leadership, inclusive of curriculum implementation support, can negatively affect children’s growth and development and child care quality. This study utilized a survey informed by the literature to examine child care directors’ characteristics, including education, experience, and pedagogical beliefs, and the influences these had on their perceptions of their leadership role and their curriculum implementation support activities. The results showed that directors' developmentally inappropriate pedagogical beliefs negatively influenced their use of curriculum support strategies. Thus, lower developmentally inappropriate pedagogical beliefs predicted the use of a greater number of curriculum support strategies. These results have implications for early childhood professional development as well as director involvement in Quality Rating Improvement System initiatives via support, training, and additional activities.
Keywords: Early childhood pedagogical leadership; Child care directors' leadership roles; Pedagogical leadership in child care centers; Curriculum implementation in chid care centers; Child care director perceptions of pedagogical leadership roles